Seroprevalence, Genetic Characteristics, and Pathogenicity of Korean Porcine Sapeloviruses - Song-Yi Kim; Choi-Kyu Park; Gyu-Nam Park; SeEun Choe; Min-Kyung Jang; Young-Hyeon Lee; Yun Sang Cho; Dong-Jun An (Viruses)
Although porcine sapelovirus (PSV) is generally subclinical, it can cause a wide range of clinical signs in some individuals, including respiratory distress, acute diarrhea, pneumonia, skin lesions, reproductive failure, and neurological diseases. In this study, we investigated the prevalence and genotype of PSV isolated from domestic pigs and wild boars in Korea. We also analyzed potential recombination events, and assessed the pathogenicity of the virus through animal experiments. In wild boars, the prevalence of PSV antibodies decreased slightly (by 1.8%) over 5 years (from 2019 to 2024); however, prevalence increased significantly (by 17.8%) in breeding sows. In samples from animals with diarrhea and respiratory clinical signs, the prevalence of PSV alone was 21.1%, whereas the prevalence of PSV mixed with other pathogens was also 21.1%. The whole genome of the PSV/Goryeong/KR-2019 strain isolated from a piglet with diarrhea was closely related to the Jpsv447 strain isolated in Japan in 2009, and recombination analysis predicted that the PSV/Goryeong/KR-2019 strain was generated by genetic recombination between the KS05151 strain and the Jpsv447 strain. However, when the PSV/Goryeong/KR-2019 strain was orally administered to 5-day-old suckling pigs, diarrhea clinical signs were mild, and no significant changes were observed in villus height and ridge depth in the duodenum, jejunum, or ileum. In addition, no neurological clinical signs were observed when the isolated virus was administered to 130-day-old pigs, and no specific lesions were found upon histopathological examination of brain tissue. In conclusion, PSV/Goryeong/KR-2019 appears to be a weakly pathogenic virus that does not cause severe diarrhea in suckling pigs, and does not cause neurological clinical signs in fattening pigs. Therefore, it is presumed that most PSVs detected in Korean pig farms are weakly pathogenic strains.